Changes in the Mouse Intestinal Microflora During Weaning: Role of Volatile Fatty Acids - Lee, Adrian (1972)
The influence of volatile fatty acids on the ecology of the bacterial flora of the mouse intestinal tract has been studied in three situations where large fluctuations in the composition of the microflora have been observed. Young mice were shown to ingest solid food particles when 11 days old; this correlated with the appearance of strictly anaerobic fusiform bacilli in the intestinal lumen and a 10,000-fold decrease in numbers of coliform bacilli. Over the same period, volatile fatty acids were shown by gas-liquid chromatography to appear in the intestinal content. It is suggested that the fusiform bacilli are responsible for the presence of the volatile acids (especially butyric acid) which exert an inhibitory effect on the coliform bacteria, resulting in the decline in numbers. When germ-free mice are placed in a specific pathogen-free mouse colony, changes in the intestinal flora occurred which were similar to those observed in the young mice approaching weaning. Once again, the decline in the coliform population correlated with the appearance of significant levels of butyric acid in the large intestine. In a further series of experiments, mice were fed penicillin and levels of the intestinal fatty acids were measured. The antibiotic eliminated the anaerobic fusiforms from the intestine, resulting in the disappearance of significant levels of butyric acid and a million-fold increase in the numbers of coliform bacilli.